Schatten's theorems on functionally defined Schur algebras - Pachara Chaisuriya; Sing-Cheong Ong (International Journal of Mathematics and Mathematical Sciences)
For each triple of positive numbers p,q,r≥1 and each commutative C*-algebra ℬ with identity 1 and the set s(ℬ) of states on ℬ, the set 𝒮r(ℬ) of all matrices A=[ajk] over ℬ such that ϕ[A[r]]:=[ϕ(|ajk|r)] defines a bounded operator from ℓp to ℓq for all ϕ∈s(ℬ) is shown to be a Banach algebra under the Schur product operation, and the norm ‖A‖=‖|A|‖p,q,r=sup{‖ϕ[A[r]]‖1/r:ϕ∈s(ℬ)}. Schatten's theorems about the dual of the compact operators, the trace-class operators, and the decomposition of the dual of the algebra of all bounded operators on a Hilbert space are extended to the 𝒮r(ℬ) setting.